Further molecular and morphological support for the formal synonymy of Anopheles subalpinus Hackett & Lewis with An. melanoon Hackett. Issue 16 (2003) - Boccolini, Daniela; Luca, MaccoDi; Marinucci, Marino; Romi, Roberto
No abstract available